Performance analysis of brushless DC motor with optimum magnetic energy for bicycle application - Muhamad Ariff Khalid; Raja Nor Firdaus Kashfi Raja Othman; Nor Aishah Md Zuki; Fairul Azhar Abdul Shukor; Md Nazri Othman; Chockalingam Aravind Vaithilingam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Brushless DC (BLDC) motor is widely used for various applications such as transportation. BLDC motor has many advantages compared to brush motor such as more compact, high robustness and simplest construction. The maintenance of this motor also low compared to brush motor due to absent of the brush inside the motor. For electric bicycle application, the conventional motor has low electromagnetic torque because not properly designed. It faces low torque density as the motor in full load condition especially during climb uphill. In this research, an optimum magnetic energy is being determine by proper selection of permanent magnet size. In addition, this research also increases the input current in dynamic condition into the designed BLDC motor. Finite element method (FEM) is used to analyze other performance characteristic of improved motor such as back electromotive force (EMF), electromagnetic torque, flux linkage, and stator flux density. Parameter for improve the current motor are selected and varied based on the required specification. In conclusion, the research proposed the new motor specification that has highest electromagnetic torque of brushless DC motor. Finally, this research provides guidelines, suggestions and proposes a better improved structure in optimize the magnetic energy in BLDC motor.